Emerging patient safety issues under health care reform: follow-on biologics and immunogenicity - Liang BA; Mackey T (Dove Medical Press, 2011)
Bryan A Liang1-3, Timothy Mackey1,41Institute of Health Law Studies, California Western School of Law, 2Department of Anesthesiology, University of California, San Diego School of Medicine, 3San Diego Center for Patient Safety, University of California, San Diego School of Medicine,4Joint Program in Global Health, University of California San Diego-San Diego State University, San Diego, CA, USAAbstract: US health care reform includes an abbreviated pathway for follow-on biologics, also known as biosimilars, in an effort to speed up access to these complex therapeutics. However, a key patient safety challenge emerges from such an abbreviated pathway: immunogenicity reactions. Yet immunogenicity is notoriously difficult to predict, and even cooperative approaches in licensing between companies have resulted in patient safety concerns, injury, and death. Because approval pathways for follow-on forms do not involve cooperative disclosure of methods and manufacturing processes by innovator companies and follow-on manufacturers, the potential for expanded immunogenicity must be taken into account from a risk management and patient safety perspective. The US Institute of Safe Medication Practices (ISMP) has principles of medication safety that have been applied in the past to high-risk drugs. We propose adapting ISMP principles to follow-on biologic forms and creating systems approaches to warn, rapidly identify, and alert providers regarding this emerging patient safety risk. This type of system can be built upon and provide lessons learned as these new drug forms are developed and marketed more broadly.Keywords: biosimilars, follow-on biologics, immunogenicity, patient safety, law, health care reform